Thermo-poroelasticity and geomechanics - Selvadurai, Antony P. S. 1942-; Suvorov, A. P. 1970- (Cambridge University Press, 2017)
Investigations of multi-physical processes in geomaterials have gained increasing attention due to the ongoing interest in solving complex geoenvironmental problems. This book provides a comprehensive exposition of the classical theory of thermo-poroelasticity, complemented by complete examples to problems in thermo-poromechanics that are used to validate computational results from multi-physics codes used in practice. The methodologies offer an insight into real-life problems related to modern environmental geosciences, including nuclear waste management, geologic sequestration of greenhouse gases to mitigate climate change, and the impact of energy resources recovery on groundwater resources. A strong focus is placed on analytical approaches to benchmark the accuracy of the computational approaches that are ultimately used in real-life problems. The extensive coverage of both theory and applications in thermo-poroelasticity and geomechanics provides a unified presentation of the topics, making this an accessible and invaluable resource for researchers, students or practitioners in the field
Title from publisher's bibliographic system (viewed on 02 Dec 2016)
Thermo-poromechanics: applications and developments -- Constitutive relationships governing thermo-poroelastic processes -- One-dimensional problems involving thermo-poroelastic processes -- Thermo-poroelasticity of geomaterial with a fluid-filled rigid 1D cavity -- Radially symmetric thermo-poroelasticity problems for a solid cylinder -- Radially symmetric thermo-poroelasticity problems: cylindrical cavity in an infinite medium -- Spherically symmetric thermo-poroelasticity problems for a solid sphere -- Spherically symmetric thermo-poroelasticity problems: spherical cavity in an infinite medium -- Glaciation problems involving thermo-poroelastic processes
Keywords: Mathematik; Thermoelasticity; Porous materials; Mechanics; Engineering geology / Mathematics